Iconicity as a cognitive linguistic concept (Journal of Human Sciences, 2024)
The  present paper deals with the concept of  “الإيقونية ”, a translation of the term Iconicity,one of the key concepts  of  cognitive linguistics. Iconicity, which is generally defined as the study of the relationship between form and meaning in a linguistic unit,  is conceived in this paper to encompass and address much of the issue of linguistic usage,particularly in the cases of words the forms of which are loaded with what suggests their meaning. The issue is broader than a mere imitation. The concept has been  applied  to examples  of Arabic language uses. The research study has also investigated to what extent iconicity was present in  the commentators’  interpretations  of some of the Quranic verses and Quranic scripts, mainly those with unfamilar word spelling and diactric forms.The research findings have highlighted the  importance of iconicity in the linguistic phenomenon and the extent of its ability to explain many linguistic uses in different contexts.